Impact of novel fuel extract variation on structural, electrical and electrochemical properties of nanostructured molybdenum oxide flakes. (2022) - Harini, R.; Latha, H.K.E.
Abstract: Nanostructured molybdenum oxide (α-MoO3 ) flakes were synthesized by solution combustion method using Shorea Robusta (Dipterocarpaceae family) leaves extract as a novel fuel and Ammonium heptamolybdate tetrahydrate (AMo) as the precursor. This article highlights the impact of fuel variation on structural, electrical and electrochemical performances of α-MoO3 prepared at different AMo to fuel ratio (1:0.25, 1:0.5, 1:1 and 1:1.5). The green synthesized α-MoO3 were characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), Brunauer Emmett-Teller (BET), Scanning electron microscopy (SEM) equipped with EDAX, High resolution transmission electron microscopy (HRTEM), UV–Visible Diffused reflectance spectroscopy (UV–Vis DRS) and Electrochemical impedance spectroscopy (EIS). XRD analysis reveals that the prepared material exhibits α-MoO3 orthorhombic structure with high crystallinity. FT-IR studies confirm the presence of MoO at 991 cm −1 . UV-DRS studies revealed the band gap varies from 3.80 eV to 4.25 eV for different fuel ratios. SEM studies illustrate the flake like structure. EIS studies reports the impedance varies from 300 Ω to 351 Ω. The band gap and impedance analysis of α-MoO3 prepared at 1:0.5 shows good conductivity compared with other ratios. HRTEM studies α-MoO3 (1:0.5) shows d-spacing of 24 nm and the selected area electron diffraction (SAED) pattern well matches with the XRD pattern. BET studies of α-MoO3 (1:0.5) shows the surface area of 6.27 m 2 g −1 with mean pore diameter of 7.26 nm. Inspected results shows improved structural, electrical and electrochemical performances for 1:0.5 α-MoO3 and hence it is proposed 1:0.5 α-MoO3 is suitable as electrode material for Li-ion batteries and sensor applications.